The ability of four species of Southern African cichlid fishes to enter deep water - Caulton, Mark S (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2026)
Using an experimental pressure chamber the rates of descent and the maximum depths of buoyancy equilibrium of some cichlid fishes were tested. Tilapia mossambica juveniles could descend to depths greater than 30 metres very rapidly. At 22°C small sub adult male fish (length ± 160 mm) could descend to a maximum buoyancy depth of 20 metres, small sub adult females to 13 metres while large adults (length ± 200 mm) of both sexes could descend to 11 metres. The fish generally take 4 to 5 days to reach their maximum equilibration depth. At 30°C mature adult male and female T.mossambica increased their maximum equilibration depth to 20 metres and at 15°C showed a decrease to a maximum depth of 6.7 metres. Temperature affects the rates of descent in a similar manner. T.rendalli can descend to 7.5 metres at 22°C. T.sparmanii can descend to 15 metres at 22°C. Hemihaplochromis philander fry and young juveniles are not affected by pressure. Adult males can descend to 16 metres at 22°C and 20 metres at 30°C. Adult females can descend to 26 metres at 22°C and 27 metres at 30°C. In T.mossambica oxygen appears to be the only gas secreted into the swimbladder to compensate for buoyancy loss. The haemoglobin of T.mossambica showed a marked Bohr and Root effect. Increased rates of descent with increased temperature are believed to be due to increased O₂ uptake, heart output etc. rather than as a direct effect of blood chemistry. The swimbladder wall of T.mossambica is extremely thin (2.8 ∕∪ m) and consequently a large amount of gas is lost through passive diffusion. Diffusion is not affected by temperature, consequently the increased secretory rates at higher temperatures are not balanced by a proportionately higher diffusion loss, thus enabling the fish to maintain a deeper buoyancy equilibrium at higher temperatures. Summary, p. 62-63.
Keywords: Cichlids -- Africa, Southern; Tilapia